1974
DOI: 10.1073/pnas.71.12.4666
|View full text |Cite
|
Sign up to set email alerts
|

The Aldehyde Content of Luminous Bacteria and of an “Aldehydeless” Dark Mutant

Abstract: Fatty aldehydes, present in the luminescent cells of Photobacterium phosphoreum and Achromobacterfischeri, and td a very slight extent in the cells of a visually dark, "aldehydeless" mutant of the latter species, were extracted, purified, and oxidized to the corresponding acids. The acids were analyzed by mass spectrometry. The results, in Cell-free extracts of lumitous bacteria that produced an NADH-activated luminescence were reported in 1953 (1). Evidence soon followed that the system required FMN (2) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 11 publications
(9 reference statements)
1
12
0
Order By: Relevance
“…Although the results presented are for B. harveyi, similar observations in vivo indicate that the conclusions are also applicable for Photobacterium fischeri (8) and P. leiognathi. The small quantities of aldehyde that could be isolated from two species of luminous bacteria were mostly of chain lengths 12, 14, and 16 carbons, in relative abundance of 5, 63, and 30%, respectively, in one species and 36, 32, and 20% in the other (14). It is also interesting that with luciferase isolated from all three Photobacterium species the rate of the reaction is much greater with tetradecanal than with aldehydes of other chain lengths, especially the naturally occurring even-numbered ones (ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results presented are for B. harveyi, similar observations in vivo indicate that the conclusions are also applicable for Photobacterium fischeri (8) and P. leiognathi. The small quantities of aldehyde that could be isolated from two species of luminous bacteria were mostly of chain lengths 12, 14, and 16 carbons, in relative abundance of 5, 63, and 30%, respectively, in one species and 36, 32, and 20% in the other (14). It is also interesting that with luciferase isolated from all three Photobacterium species the rate of the reaction is much greater with tetradecanal than with aldehydes of other chain lengths, especially the naturally occurring even-numbered ones (ref.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro reaction involves the mixed function oxidation of FMNH2 and a long-chain aliphatic aldehyde to give the corresponding acid and light emission. Pure Beneckea harveyi luciferase is not highly specific with regard to aldehyde chain length (8)(9)(10)(11)(12)(13)(14) carbons), even though. some distinctions can be made, especially with luciferases from different bacterial species (3,4).…”
mentioning
confidence: 99%
“…Aristolene with the following biological activity: has a smell that attracts predators and wolves (Scrivner et al, 1984), is an antibiotic bacterium, Bacillus, and is used for throat congestion (Zour), it is anti-inflammatory, the cradle of the nerves (Tian-Shung et al, 2004), pain reliever and has luminous bacteria (Shimomura et al, 1974); 4. 7-Hexadecenal with the following biological activity: used for treating patients with diabetes, by increasing the secretion of insulin in the body (Turgumbayeva et al, 2015), it is found in the liver of sheep and thus attractive to wolves and used in hunting wild animals (Scrivner et al, 1984), has Luminous Bacteria "Aldehydeless" Dark Mutant (Shimomura et al, 1974); 5. Tricosene which has kairomone effect (Ananthakrishnan et al, 1991).…”
Section: Induction Of Biochemical Active Constituents From Jojoba Callusmentioning
confidence: 99%
“…These major active constituents are divided into five fractions: 1. 1-Hexadecanol which has the following biological activity: a composite medium used in the synthesis of other compounds (Turgumbayeva et al, 2015), has flavors and smells like composite simmondsin (Scrivner et al, 1984) and has luminous bacteria (Shimomura et al, 1974); 2. nonadecatriene compound acting as pheromone that attracts male insects (Nilsson, 2009); 3. Aristolene with the following biological activity: has a smell that attracts predators and wolves (Scrivner et al, 1984), is an antibiotic bacterium, Bacillus, and is used for throat congestion (Zour), it is anti-inflammatory, the cradle of the nerves (Tian-Shung et al, 2004), pain reliever and has luminous bacteria (Shimomura et al, 1974); 4.…”
Section: Induction Of Biochemical Active Constituents From Jojoba Callusmentioning
confidence: 99%
See 1 more Smart Citation